2011
DOI: 10.1165/rcmb.2010-0451oc
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Groups Mediate the Immunomodulatory Effects of Volatile Anesthetics in Acute Cell Injury

Abstract: Volatile anesthetics are known to attenuate inflammatory response and tissue damage markers in acute organ injury. It is unclear whether these beneficial effects of volatile anesthetics are mediated by the ether basic structure or by characteristics of their halogenations. We describe in an in vitro model of acute inflammation in pulmonary cells that halogenation (fluorinated carbon groups) is responsible for the immunomodulatory effects. The inflammatory response after coexposure to endotoxin and sevoflurane,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
2
32
0
3
Order By: Relevance
“…The blocks were again randomized into the following groups: (1) LPS group (n = 10), which received intravenous 1 mg/kg Escherichia coli endotoxin [LPS, E. coli endotoxin serotype 055:B5; Sigma-Aldrich, Buchs, Switzerland; dissolved at a concentration of 1 mg/ml in phosphate-buffered saline (PBS) Kantonsapotheke Zurich, Zurich, Switzerland]; (2) LPS1HFIP group (n = 7), which was treated identically to the LPS group with the additional administration of 67 mg/kg HFIP (SigmaAldrich) in Ringer's lactate for 30 min after LPS injection; (3) LPS1sevoflurane group (n = 8), which was treated identically to the LPS group but with the additional administration of sevoflurane (Sevorane; Abott, Baar, Switzerland) using the Anaesthetic Conserving Device (AnaConDa; Sedana Medical, Uppsala, Sweden) for 30 min after LPS injection [18] while propofol infusion was stopped and reinitiated after the 30-min sevoflurane application; (4) control group with PBS instead of LPS (n = 5); (5) HFIP group in which animals received PBS and 67 mg/kg HFIP (n = 5). Based on results from in-vitro studies [19], we decided empirically to administer a dose of 67 mg/kg HFIP to rats, which corresponds to 0Á39 mmol/kg total body weight (BW) or 4 mmol/l blood volume. This dose is comparable to previous experiments [14,19] and significantly lower than the median lethal dose (LD 50 ) (approximately 180 mg/kg in mice when administered intravenously) [14].…”
Section: Design Of Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The blocks were again randomized into the following groups: (1) LPS group (n = 10), which received intravenous 1 mg/kg Escherichia coli endotoxin [LPS, E. coli endotoxin serotype 055:B5; Sigma-Aldrich, Buchs, Switzerland; dissolved at a concentration of 1 mg/ml in phosphate-buffered saline (PBS) Kantonsapotheke Zurich, Zurich, Switzerland]; (2) LPS1HFIP group (n = 7), which was treated identically to the LPS group with the additional administration of 67 mg/kg HFIP (SigmaAldrich) in Ringer's lactate for 30 min after LPS injection; (3) LPS1sevoflurane group (n = 8), which was treated identically to the LPS group but with the additional administration of sevoflurane (Sevorane; Abott, Baar, Switzerland) using the Anaesthetic Conserving Device (AnaConDa; Sedana Medical, Uppsala, Sweden) for 30 min after LPS injection [18] while propofol infusion was stopped and reinitiated after the 30-min sevoflurane application; (4) control group with PBS instead of LPS (n = 5); (5) HFIP group in which animals received PBS and 67 mg/kg HFIP (n = 5). Based on results from in-vitro studies [19], we decided empirically to administer a dose of 67 mg/kg HFIP to rats, which corresponds to 0Á39 mmol/kg total body weight (BW) or 4 mmol/l blood volume. This dose is comparable to previous experiments [14,19] and significantly lower than the median lethal dose (LD 50 ) (approximately 180 mg/kg in mice when administered intravenously) [14].…”
Section: Design Of Animal Experimentsmentioning
confidence: 99%
“…For gene expression analysis, cells were exposed for 6 h to 20 mg/ml LPS (dissolved in PBS) from E. coli serotype 055:B5 (Sigma-Aldrich) to induce an inflammatory response (control cells were incubated with PBS) and co-exposed to 8 mmol/l HFIP (Sigma-Aldrich), as in our previous study [13] (Fig. 1b).…”
Section: Design Of the Experiments With Hmvecmentioning
confidence: 99%
See 1 more Smart Citation
“…45 In vitro studies in epithelial and endothelial cells suggest that halogenation (fluorinated carbon groups) is responsible for the immunomodulatory effects of volatile anesthetics. 46 The trifluorocarbon (CF 3 ) molecule, which is shared in all newer volatile anesthetics, has been suggested as the specific molecular group of a volatile anesthetic that exerts immunomodulatory effects (Figure 2). In pulmonary epithelial and endothelial cells, modulation of chemical structures of volatile anesthetics showed that the CF 3 molecular group is required for decreasing multiple proinflammatory chemokine and cytokine markers after LPS treatment.…”
Section: Volatile Anesthetics and Renal Protection Mechanismsmentioning
confidence: 99%
“…It is possible that they might come from inflamed cells in the CNS via leakage through a compromised blood-brain barrier (BBB) or directly from peripheral immune cells sensitive to sevoflurane. It has been postulated that the immunomodulatory effects of volatile anesthetics on peripheral immune cells can be mediated by trifluorocarbon (CF 3 ) groups found on halogenated molecules [40].…”
Section: Discussionmentioning
confidence: 99%